Proteomic analysis of soybean cyst nematode (The Journal of Plant Protection Sciences, 2021)
The soybean cyst nematode (SCN, Heterodera expression in SCN during its life cycle from J2  glycines) is the major pest of soybean in the to adult. In recent years, the application of  U.S. Infections of soybean by SCN include proteomic tools such as two-dimensional  chlorosis, root necrosis, loss in seed yield and polyacrylamide gel electrophoresis (2D suppression of growth of root and shoots. PAGE), matrix-assisted laser desorption  Chemical control for soybean is not normally /ionization time of flight mass spectrometry  used because economic and environmental ( M A L D I - T O F - M S ) , a n d l i q u i d costs of the few effective treatments are chromatography - mass spectrometry (LC-MS)  prohibitive.
Keywords: soybean; chromatography - mass spectrometry; electrophoresis (